Thalassaemia. - Higgs, D; Engel, J; Stamatoyannopoulos, G (2012)
Thalassaemia is one of the most common genetic diseases worldwide, with at least 60,000 severely affected individuals born every year. Individuals originating from tropical and subtropical regions are most at risk. Disorders of haemoglobin synthesis (thalassaemia) and structure (eg, sickle-cell disease) were among the first molecular diseases to be identified, and have been investigated and characterised in detail over the past 40 years. Nevertheless, treatment of thalassaemia is still largely dependent on supportive care with blood transfusion and iron chelation. Since 1978, scientists and clinicians in this specialty have met regularly in an international effort to improve the management of thalassaemia, with the aim of increasing the expression of unaffected fetal genes to improve the deficiency in adult β-globin synthesis. In this Seminar we discuss important advances in the understanding of the molecular and cellular basis of normal and abnormal expression of globin genes. We will summarise new approaches to the development of tailored pharmacological agents to alter regulation of globin genes, the first trial of gene therapy for thalassaemia, and future prospects of cell therapy.